Image of Wojciech Drewaniak in his books “History Without Censorship”. Discursive analysis of image traits: “passionate” and “has great historical knowledge” - Barańska-Szmitko, Anna; Agnieszka Gralak (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The aim of the chapter is to illustrate the method of discursive analysis of image realized on the empirical material on the example of a research related to Wojciech Drewaniak – YouTuber and author of books from the “History Without Censorship” series. Two among over a dozen image traits were analyzed. The key features of communicating the “passionate” features turn out to be emphasizing the importance of the topics covered; while communicating knowledge ("has great historical knowledge") is realized through mentioning dates and historical details.